Label-free quantitative phase biological imaging for assessment of cell maturation status and organoid function - Rachmawisista, Adrianzka Mayreswara Dewa (Nanyang Technological University, 2022)
Quantitative Phase Imaging (QPI) is a technique that has the potential to be used for cell dry mass monitoring due to its non-labeled nature, increased sensitivity, and linear correlation between phase and cell dry mass. Various QPI implementations such as DPM and MISS have shown good performance for cellular imaging. These imaging techniques show great potential to monitor the cell maturity status by computing the dry mass density from the phase map. In this project, we will explore implementing a cardiomyocyte cell dry mass measurement system using DPM and MISS systems. We will also develop software to find the dry mass density of the cell samples. This report showcases the principle of QPI systems, the software required to run them, and how we can implement the system. We showed that QPI has the potential to create a cell maturity monitoring system by comparing young and mature cardiomyocyte cells.